Effectiveness of DRTA Strategy in Improving the Reading Skills - Ana Margarita Abogadil Agao-Agao (Randwick International of Education and Linguistics Science Journal, 2023)
This study aimed to evaluate the reading level of the grade 7 learners before and after the conduct of intervention and to determine the effectiveness of Directed Reading-Thinking Activity (DRTA). The reading level was measured using the Philippine Informal Reading Inventory (Phil-IRI) tool where word recognition and comprehension are the variables used. On word recognition, mispronunciation, repetition, substitution, omission, insertion, reversal and transposition are considered miscues while the comprehension level was determined by the scores in the comprehension questions. Reading level is determined by their level in word recognition and comprehension taken from the Phil-IRI formula. The researcher used experimental group of respondents in teaching reading using the DRTA. The respondents are the grade 7 learners of Mindanao State University-Maguindanao who experienced modular learning for the last two school years in elementary, 2020 – 2022. The study was conducted in September to October 2022. The instruments are the reading selection consisting of 134 words and the 10 comprehension questions. Results revealed that there is a significant difference on respondents’ reading level in terms of word recognition with the t-value -8.388 and comprehension with t-value -14.357 after the use of Directed Reading-Thinking Activity (DRTA). It is therefore concluded that DRTA has a positive effect in improving the reading skills of the grade VII.